Žinių vadybos įtaka darnaus vystymosi reikšmėms įgyvendinti organizacijoje - Atkočiūnienė, Zenona Ona Ona; Radiunaitė, Renata (Information & Media, 2011)
Pastaraisiais metais darnus vystymasis tampa viena populiariausių ir ambicingiausių visuomenės raidos ideologijų. Socialinių, ekonominių ir aplinkosauginių iniciatyvų harmonija organizacijos kontekste yra sudėtingas procesas, vedantis prie visiškai naujos XXI amžiaus verslo formuluotės. Tačiau darni organizacija nėra savaiminis reiškinys; jai įgyvendinti būtina sukurti tinkamas sąlygas: identifikuoti darnos iniciatyvų organizacijoje veiksnius, juos skatinančią ir palaikančią vadybos sistemą, nuolat juos plėtoti ir tobulinti. Intelektinio kapitalo svarba, nuolatinis mokymasis, dalijimasis žiniomis yra priskiriami prie veiksnių, lemiančių darnų organizacijos vystymąsi, tačiau požiūris į žinių vadybą kaip į visus įvardytus veiksnius jungiančią vadybos sistemą nėra visiškai suformuluotas. Nėra apibrėžtas ir žinių vadybos raiškos būdų bei darnaus organizacijos vystymosi veiksnių tarpusavio ryšys. Šio straipsnio tikslas – nustatyti organizacijos žinių vadybos ir darnaus vystymosi sąsajas, sukurti darnios žinių organizacijos modelį.Pagrindiniai žodžiai: žinių vadyba, žinių organizacija, žinių kultūra, darnus vystymasis, darni organizacija, intelektinis kapitalas.Knowledge Management Influence on Implementing Sustainable Development Means in OrganizationsZenona Ona Atkočiūnienė, Renata RadiunaitėSummaryRecently, sustainable development has become one of the most popular and ambitious ideologies of the evolution of society. The harmony of social, economic and environmental initiatives in the context of organization is a very difficult process which leads to a completely different business formula of the 21st century.However, a sustainable organization is not a self-phenomenon. In order to implement it, proper conditions need to be created: identification of factors that influence sustainable initiatives in the organization, establishment of a managerial system that promotes and supports these factors, and their continuous development and refinement. The intellectual property, knowledge sharing and continuous competence improvement are labelled as elements influencing the sustainable development of an organization. These elements are also significant factors in knowledge management, although no direct correlation has been found between sustainable development and knowledge management. The aim of the article is to identify connections between knowledge management and sustainable development in an organization and to create the model of a sustainable knowledge organization. In order to adjust to the continuously changing environment and to develop proper competencies for the increasing needs of sustainable society, an organization needs to implement knowledge management concurrently with the evolution of the concept of sustainable development, because sustainability itself implicates the ability to adapt to global changes.Keywords: knowledge management, knowledge organization, knowledge culture, sustainable development, sustainable knowledge organization, intellectual capital.